Seafloor Mapping – The Challenge of a Truly Global Ocean Bathymetry - Wölfl, Anne-Cathrin; Snaith, Helen; Amirebrahimi, Sam; Devey, Colin W.; Dorschel, Boris; Ferrini, Vicki; Huvenne, Veerle A. I.; Jakobsson, Martin; Jencks, Jennifer; Johnston, Gordon; Lamarche, Geoffroy; Mayer, Larry; et al. (Frontiers in Marine Science, 2019)
Detailed knowledge of the shape of the seafloor is crucial to humankind. Bathymetry data is critical for safety of navigation and is used for many other applications. In an era of ongoing environmental degradation worldwide, bathymetry data (and the knowledge derived from it) play a pivotal role in using and managing the world’s oceans in a way that is in accordance with the United Nations Sustainable Development Goal 14 - conserve and sustainably use the oceans, seas and marine resources for sustainable development. However, the vast majority of our oceans is still virtually unmapped, unobserved, and unexplored. Only a small fraction of the seafloor has been systematically mapped by direct measurement. The remaining bathymetry is predicted from satellite altimeter data, providing only an approximate estimation of the shape of the seafloor. Several global and regional initiatives are underway to change this situation. This paper presents a selection of these initiatives as best practice examples for bathymetry data collection, compilation and open data sharing as well as the Nippon Foundation-GEBCO (The General Bathymetric Chart of the Oceans) Seabed 2030 Project that complements and leverages these initiatives and promotes international collaboration and partnership. Several non-traditional data collection opportunities are looked at that are currently gaining momentum as well as new and innovative technologies that can increase the efficiency of collecting bathymetric data. Finally, recommendations are given towards a possible way forward into the future of seafloor mapping and towards achieving the goal of a truly global ocean bathymetry.